Four new species of the genus Lobrathium Mulsant & Rey (Coleoptera: Staphylinidae: Paederinae) from China - Weber, Xiao-Yan Li; Solodovinikov, Alexey; Zhou, Hong-Zhang (Zootaxa, 2013)
Four new species of the genus Lobrathium Mulsant & Rey, 1878 from the mainland China are described: L. quadrum sp. n. from Sichuan, L. rutilum sp. n. from Hubei, L. tortuosum sp. n. from Zhejiang and L. zonalis sp. n. from Sichuan. In addition, the paper reviews the history of the research on the Chinese fauna of the genus. Some important morphological characters are illustrated for the new species.